Contribuições aos requisitos de projeto no processo do retrofit - Melo, Adriana Virgínia Santana; Cunha, Alana Santos; Santos, Priscilla Vanessa Pereira; Ferreira, Emerson de Andrade Marques; Costa, Dayana Bastos (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The retrofit is a process that allow buildings existent to have its improved the performance, but many problems are identified during the design and construction. The project requirement should consider that building existent can link factors success during identify client's requirement. The research features the confrontation of the Brazilian Standard with the stock of buildings of the city of Salvador / Ba, with result if exhibit the relationship between different system and components absents in the building existent for use age. The product this paper enables the view the different Brazilian standard between building existent in the 1940 at 2019 where client can acknowledge the parameters the obsolescence the building for system, and get collaborate too in direction for hierarchic the client's requirement.